A Study on Camphor Derivatives and Its Applications: A Review - Anjaneyulu, Bendi; Sangeeta; Saini, Naina (Current Organic Chemistry, 2021)
Natural compounds are the prominent sources for the synthesis of abundant biologically active substances in medicinal chemistry. Camphor exists in two enantiomeric forms i.e., R and S, or both, which are readily obtainable. Camphor is a small molecule with chirality property that binds to some active site, together with its low cost and convenience to transform into synthetically useful derivatives and one of the most important monoterpenoids widely spread in plants and has been used as starting material for the various camphor based derivatives which exhibit several biological activities include antimicrobial, antiviral, antioxidant, analgesic and anti-cancer. Many of those simple derivatives are commercially available in the form of camphor sulfonic acid or ketopinic acid that can be easily be produced from camphor. This compound is primarily used as a chiral starting material in the enantiospecific synthesis of natural products is because of its available methods for the direct or indirect introduction of functionality at C-3, C-5, C-8, C-9, and C-10 carbon atoms. In this study, heterocyclic compounds derived from camphor are arranged in different groups as Camphor-Derived Simple Heterocycles, Fused Camphor-Derived Heterocycles, Spiro Camphor-Derived Heterocycles, Ring Expanded Camphor-Derived Heterocycles and Camphor derived metal complexes. This study summarizes the transformations of camphor and its derivatives along with their biological activities.
Keywords: organic synthesis